2004
DOI: 10.1051/0004-6361:20035960
|View full text |Cite
|
Sign up to set email alerts
|

Propagating waves in the sunspot umbra chromosphere

Abstract: Abstract. We investigate the line-of-sight velocity oscillations in the sunspot NOAA 0051 during its disk transit. The data obtained in this study provide evidence for the existence of running umbral waves in the chromosphere. These waves have a period of 2.8 min and propagate from the sunspot center outward with the phase velocity of 45-60 km s −1 with the line-of-sight velocity amplitude of about 2 km s −1 . In most cases the waves terminate rather abruptly on the umbra boundary and show no direct linkage wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 21 publications
4
29
0
2
Order By: Relevance
“…Both the early works (Sigwarth & Mattig 1997;Kobanov & Makarchik 2004;Tziotziou et al 2006) and recent publications based on SDO data analysis note that lowfrequency oscillations concentrate in regions where the magnetic field lines are significantly inclined (i.e., in the penumbra), whereas the 5 mHz and higher frequency oscillations are concentrated within the umbra boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…Both the early works (Sigwarth & Mattig 1997;Kobanov & Makarchik 2004;Tziotziou et al 2006) and recent publications based on SDO data analysis note that lowfrequency oscillations concentrate in regions where the magnetic field lines are significantly inclined (i.e., in the penumbra), whereas the 5 mHz and higher frequency oscillations are concentrated within the umbra boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…This way, the stratification with height of wave parameters like velocity amplitude, as well as their phase variations and their distribution with frequency can be determined. From these parameters, some authors have suggested that the three-minute chromospheric oscillations above sunspot umbrae are standing acoustic waves , while others found them to be propagating waves able to reach the upper layers of the solar atmosphere Banerjee et al, 2002;O'Shea et al, 2002;Brynildsen et al, 2003Brynildsen et al, , 2004Kobanov and Makarchik, 2004). The typical sawtooth pattern of propagating shock wave fronts has been made patent in many observations using different chromospheric and transition region lines (see, e.g., Rouppe van der Voort et al, 2003;Centeno et al, 2006;Tian et al, 2014).…”
Section: Propagation From the Photosphere To The Chromospherementioning
confidence: 98%
“…Tsiropoula et al (2000) showed several clear cases where waves that originate inside the umbra continue to propagate in the penumbra. However, the often abrupt termination of three-minute wave patterns at the umbra/penumbra boundary was noted by Kobanov and Makarchik (2004) and Kobanov et al (2006). Not all three-minute wave fronts can be traced out from the umbra into the penumbra.…”
Section: Chromospheric Running Penumbral Wavesmentioning
confidence: 99%
“…These waves, considered to be magnetoacoustic modes, were observed to propagate with a phase velocity of 10-20 km s −1 and exhibited intensity fluctuations in the range of 10%-20%. Brisken & Zirin (1997) and Kobanov & Makarchik (2004) have revealed how the frequencies and phase speeds of RPWs vary from 3 mHz, 40 km s −1 to 1 mHz, 10 km s −1 from the inner penumbral boundary to the outer penumbral edge, and becomes gradually invisible while approaching the outer boundary of the penumbra. Additionally, Kobanov (2000) has observed the propagation of RPWs in the chromosphere up to ∼15″ (∼10,000 km) from the outer edge of the penumbral boundary, suggesting the quiet-Sun p-mode oscillations dominate at greater distances, hence overpowering the signatures of any remaining RPWs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is also evidence that umbral oscillatory events of the chromosphere are not the source of RPWs (Giovanelli 1972;Moore & Tang 1975;Christopoulou et al 2000Christopoulou et al , 2001Tziotziou et al 2002;Kobanov & Makarchik 2004;Bloomfield et al 2007). For example, Christopoulou et al (2001) reported that RPWs are more closely associated with photospheric umbral oscillations than the chromospheric ones.…”
Section: Introductionmentioning
confidence: 99%